Exposure to violence during the vocational training of resident physicians - Montes-Villaseñor, Evangelina (Universidad Autónoma de Tamaulipas, 2018)
The Medical residencies guarantee the academic and human apprenticeship and training of the future medical specialists. Nevertheless, there is evidence of maltreatment, discrimination and abuse against the medical residents. The purpose of this work was to identify experiences of physical, psychological or sexual violence of medical residents in the state of Veracruz, Mexico. A cross-sectional quantitative analysis was carried out focusing on a population of 656 residents from 16 receiving medical centers during 2014. Results indicate that 87 % reported at least one experience of physical violence during their medical internship as specialists. Additionally, and up to 50.46 % it reported psychological violence. The main aggressors were reported to be chiefs of service (33.5 %) and resident partners (33.5 %) and participants were more affected during the morning shift (34.76 %). 51.52 % of the participating population are males and 48.48 % are females. As regards The bivariate analysis revealed the following results: correlation between gender and psychological violence: X2 = 9.740 6, P = 0.004; physical violence: X2 = 4.876 4, P = 0.003; and sexual violence: X2 = 4.868 4, P = 0.001. Males reported higher aggression rates in their medical internships since they were subject to higher levels of psychological, physical and sexual violence. The results of the study emphasize the importance of forging institutional values as an integral part of medical residency programs. Respect and the dignity among medical residents, superiors and health professionals who are involved in training and apprenticeships of specialists should be promoted.